Hotel Assessment through Social Media: The case of TripAdvisor - Molinillo,Sebastian (2016)
Hotel booking decisions are increasingly influenced by consumer feedback available on social media sites. Using data submitted by customers on TripAdvisor, this study analyzes the customer satisfaction ratings posted for 2,211 hotels. The study provides four key contributions to our knowledge on this subject. Firstly, a comparative analysis was conducted of customer ratings for hotels located on the Spanish coast and Portugals southern coast. Secondly, significant differences were found in the number of comments and average online review ratings, which showed a correlation to the tourism destinations geographical locations. Thirdly, the study found that customers tend to rate their hotel experiences positively. Fourthly, the customers overall level of satisfaction with a hotel tends to increase proportionately based on the number of customer feedback comments posted for that hotel. Consequently, one of this studys findings is that hotels should encourage their customers to post comments on customer review websites to balance out any negative feedback.